Development and characterization of Mecitentan loaded self-micro emulsifying drug delivery system - Vandana Chaudhary, Punit B. Parejiya, Pranav C. Patel, Niravbhai J. Patel, Romit Jani, Dhaval P. Patel (South Eastern European Journal of Public Health, 2025)
Introduction: Mecitentan is a selective endothelin receptor antagonist used in the treatment of pulmonary arterial hypertension (PAH). However, its poor solubility significantly limits its bioavailability. To overcome this challenge and enhance the drug’s therapeutic efficacy, a novel self-micro emulsifying drug delivery system (SMEDDS) was explored. SMEDDS are isotropic mixtures of oil, surfactants, and cosurfactants that form fine oil-in-water emulsions upon contact with gastrointestinal fluid, which are absorbed into the lymphatic pathways, bypassing the first-pass hepatic effect. Objectives: The objective of this study was to develop and evaluate a SMEDDS formulation for Mecitentan that addresses its solubility issues and enhances its bioavailability. Methods: In the formulation, oleic acid, Labrafil M 2125 CS, PEG-400, and Labrasol ALF were selected as the mixed oil, surfactant, and cosurfactant, respectively. The formulation was assessed for droplet size, polydispersity index (PDI), zeta potential, and drug release rate. The resulting SMEDDS was characterized in terms of these parameters to determine its potential in improving the release and bioavailability of Mecitentan. Results: The droplet size of the SMEDDS formulation ranged from 37.8 to 176 nm, with a PDI value of 0.271, indicating a narrow size distribution. The zeta potential was measured at -1.6 mV, and the formulation exhibited an 81.50% drug release, suggesting significant enhancement in the release profile of Mecitentan. Conclusions: The self-micro emulsifying drug delivery system (SMEDDS) was found to be effective in improving the drug release and bioavailability of Mecitentan, addressing its solubility limitations and offering a promising strategy for enhancing its therapeutic efficacy in the treatment of pulmonary arterial hypertension.